Aliphatic amines at the Cape Verde Atmospheric Observatory: Abundance, origins and sea-air fluxes. (15th April 2019) - van Pinxteren, Manuela; Fomba, Khanneh Wadinga; van Pinxteren, Dominik; Triesch, Nadja; Hoffmann, Erik Hans; Cree, Charlotte H.L.; Fitzsimons, Mark F.; von Tümpling, Wolf; Herrmann, Hartmut
Abstract: Aliphatic amines are important constituents of the marine environment. However, their biogenic origins, formation processes and roles in atmospheric chemistry are still not well understood. Here we present measurements of monomethylamine (MMA), dimethylamine (DMA) and diethylamine (DEA) from two intensive sampling campaigns at the Cape Verde Atmospheric Observatory (CVAO), a remote marine station in the tropical Atlantic Ocean. The amines were measured in the sea surface microlayer (SML), in bulk seawater, in the gas and the submicron particulate aerosol phase. Additionally, a 24-month record of amine concentrations in aerosol particles, together with other particle constituents and biological and meteorological parameters, is presented. In the SML, mean amine concentrations were in the range 20–50 nmol L −1 . The correlation of the amines to chlorophyll-a (R 2  = 0.52) and the abundance of the diatom pigment fucoxanthin may indicate that amines were formed via algal production. Amine concentrations in the gas and particulate aerosol phases were dominated by DMA, with average concentrations of 4.5 ng m −3 and 5.6 ng m −3, respectively. Average MMA concentrations were 0.8 ng m −3 in the gas phase and 0.2 ng m −3 in the particle phase. DEA was present in the particle phase with an average concentration of 3.9 ng m −3, but was not detected in the gas phase. Sea to air fluxes for MMA and DMA were calculated from the seawater and gaseous amine concentrations; these varied from −8.7 E−14 to +4.0 E−13 mol m −2 s −1 and from −1.9 E−12 to +2.17 E−12 mol m −2 s −1, respectively. While the flux for MMA was mainly positive, suggesting an oceanic source for this analyte, the flux for DMA could be both positive and negative, indicating that 2-way transport may be occurring. Principal component analysis of the 24-month dataset of amines in aerosol particles revealed that the particulate amines were not directly linked to the identified sources. It seems that the transfer of amines was being determined by gas to particle conversion rather than via primary processes. The correlation of both seawater- and gas phase-amines with biological indicators suggests that they were partly linked and that the amine abundance in the atmosphere (gas phase) reflected biological processes in seawater. In contrast, particulate amine concentrations did not show such a direct response and might have other significant sources and environmental drivers. Graphical abstract: Image 1 Highlights: Aliphatic amines are present in the tropical remote Atlantic Ocean and Atmosphere. Amines in the seawater and gas phase are connected to biological activity. Ocean can be a sink or a source of amines. Sources of amines in the submicron particle phase are probably not of primary nature.